The Role of Blockchain Technology and Its Impact on The Buyer-Supplier Relationships in The Food Supply Chain - Melanthiou, Yioula; El Naddaf, Sami; Efthymiou, Leonidas; Christodoulou, Klitos (My University, 2024)
Blockchain technology (BCT) is a decentralized consensus system that provides secure, transparent record-keeping through digital cryptocurrency (Shankar et al., 2017). Blockchains allow us to have a distributed peer-to-peer network where non-trusting members can verifiably interact with each without the need for a trusted authority (Christidis and Devetsikiotis, 2016). In recent years, blockchain (BC) networks have expanded to a broad spectrum of fields. They have garnered significant attention due to their feature of creating secure private and public networks in a decentralized manner. On the other hand, the expansion of the food industry, both on the national and the global stages, has resulted in complex collaborative networks where supply chains food safety and management significantly affect public health and has become an essential subject of concern in both print and digital media around the globe. The traditional Food Supply Chain fails to meet the customer requirements of quality, safety, reliability, transparency, and traceability (Tayal et.al., 2020). The use of blockchain-based systems for managing a supply chain offers significant benefits, such as faster and more reliable traceability (Katsikouli et al., 2020). There is a pressing need to study Blockchain technology especially in the food supply chain. Moreover, conceptual and empirical contributions will improve our understanding of this emerging technology and its impact on food supply chains. Buyers in the food industry are requesting nowadays updated data on nourishments through the presence and use of digital media. They are likewise progressively requesting to know whether the nourishments they devour are ecologically and socially manageable or not. As an outcome, food product traceability, safety, and sustainability issues have become urgent worries to food retailers, wholesalers, processors, and farmers. Digitalization permits food supply chains to be exceptionally associated, proficient, and receptive to customer needs and regulation requirements (Kittipanya-ngam and Tan, 2019). Blockchain technology offers significant advantages in the food supply chain by enabling immediate identification and prevention of tampering, benefiting both food producers and retailers. Additionally, it addresses the issue of information asymmetry, potentially reducing market failures caused by consumers inadvertently selecting lower quality or unsafe food due to a lack of transparent information about food quality. The purpose and the importance of this abstract lay upon the role of Blockchain technology and its impact on buyer-supplier relationships in the food industry. It is very important to understand the effect of such role of Blockchain technology since the agri-food industry could benefit from the introduction of Blockchain, which has all the features to represent a huge sustainable business model (SBM) innovation towards sustainability (Tiscini et al., 2020). The management culture adopted for food supply chains has an impact on the quality of the end product and the vitality of the involved businesses. As for the methodology, different steps will take place: the first step is about conducting a comprehensive review of existing literature on blockchain technology, buyer- supplier relationships and their application in the food supply chain- by analyzing the dynamics of buyer-supplier relationships within the food supply chain, considering factors like trust, communication, information sharing, and power dynamics, while evaluating the influence of blockchain technology on these relationships, including its impact on transparency, trust-building, and collaborative decision-making; the second step, is about selecting case studies from the food industry where blockchain technology has been implemented or explored to enhance buyer-supplier relationships, and by illustrating its impact on various aspects of supply chain dynamics, transparency, and efficiency; the third step is about conducting semi-structured interviews with stakeholders involved in the food supply chain including food producers, distributors, retailers and even consumers to gather primary data on their experiences and perceptions regarding blockchain technology, and along collecting secondary data from reports, industry publications, and academic journals to supplement primary data and provide additional context. It is important to mention that the collected information from the food companies through different interviews with the managers or supervisors will help in interpreting and analyzing the academic literature and mainly notify any future research opportunities (Wang et al., 2018). Regarding the contributions, this study will provide a comprehensive understanding of blockchain technology's role in addressing challenges within the food supply chain, such as traceability and transparency. It highlights the potential benefits of blockchain-based systems and their impact on traditional supply chain management practices. Additionally, the study offers insights into buyersupplier relationships in the food industry, examining how blockchain influences collaboration, trustbuilding, and information sharing. By synthesizing academic literature and empirical data, the research identifies future research opportunities to further explore blockchain's potential in improving supply chain operations and sustainability. Furthermore, this study will empower managers to make informed decisions about integrating blockchain-based systems into supply chain operations. Furthermore, by deepening understanding of blockchain's impact on buyer-supplier relationships, managers can foster collaboration and trust, streamline communication, and improve overall supply chain performance. Additionally, the study emphasizes blockchain's potential to drive innovation and sustainability, enabling managers to develop more environmentally and socially responsible business models while meeting customer demands for quality and transparency. Finally, the research question that is formulated is settled as “what is the role of Blockchain Technology and its influence on the Buyer-Supplier Relationships in the Food Supply Chain? This research, which integrates information technology, Blockchain, operation management and supply chain, will motivate the academia and industry to adopt and achieve efficient and effective goals in this field of Food Supply Chain.
Keywords: Blockchain Technology; Buyer-Supplier Relationships; Transparency; Food Supply Chain; Digitalization; Traceability; Safety and Sustainability Issues